IMPLEMENTASI PEMBIASAAN AGAMIS DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Al Muftiyah; Imam Mashuri (INCARE, International Journal of Educational Resources, 2023)
This study aims to describe the habit of praying Dhuha which is carried out by students in MI Miftahul Ulum Karanganyar grades I to grade VI. The role of the teacher as a guide in the implementation of Dhuha prayer. This type of research is qualitative research. Collection is done by interview, documentation. The results of this research show that the habituation of Dhuha prayer and tahlil reading by the teacher in forming the character of students is suitable for the purpose, namely it is already running according to the school program. The teacher acts as an educator as well as an activity companion, consultant, role model, activity designer and problem solver. The obstacles encountered in implementing this activity are that there are still many students who arrive late so they don't match the predetermined schedule.